Adaptations of Euro-Canadian schools to Inuit culture in selected communities in Nunavut - Berger, Paul (2001)
This study explores educators' current and desired 'adaptations' of Euro-Canadian schools to Inuit culture, in five communities in one region of Nunavut Communities ranged in size from 800 to 3500 residents, of which on average 90% are Inuit. Primary data collection occurred in the five communities through taped interviews with 20 educators, as well as informal conversations with 8 educators, in April, 2000. All those who volunteered to take part after hearing a description of the study, became participants. 1 of the 20 participants in the formal interviews, and 1 of the 8 in the conversations were Inuit. All other participants were from Southern Canada. This study creates a reference to current and desired 'adaptations' which can be used by educators in Nunavut when considering change. Reported and desired 'adaptations' are grouped into seven themes. Very few instances were reported where community input was solicited, desired, or used in determining the direction of the schools, or where schools explicitly taught Inuit values. Examples were given of attempts to incorporate 'Inuit curriculum' into schools, or the desire to do so, and many practices were documented which are educators' attempts to interact with students 'like Inuit do'. As well as adaptations toward Inuit culture, many changes were reported or desired which are current Southern practices, teaching ESL practices, or practices designed to respond to the effects on students of societal problems.